2020
DOI: 10.1021/acsaem.0c00362
|View full text |Cite
|
Sign up to set email alerts
|

Tannic Acid-Mediated In Situ Controlled Assembly of NiFe Alloy Nanoparticles on Pristine Graphene as a Superior Oxygen Evolution Catalyst

Abstract: Controlled assembly of small and highly dispersed earth-abundant transition metal-based oxygen evolution reaction (OER) catalysts on pristine graphene could greatly boost the OER efficiency while significantly reducing the cost, but this presents great challenges. Pristine graphene (rather than reduced graphene oxide or graphene with a damaged electronic structure) supported NiFe alloy nanoparticles (NPs) have been synthesized for the first time via tannic acid (TA)-mediated in situ controlled assembly, in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 67 publications
1
23
0
Order By: Relevance
“…As shown in Figure 6 e, Ni 5 P 4 /Ni 2 P–FeNi@C presents a larger C dl value (8.01 mF cm −2 ) than Ni 5 P 4 /Ni 2 P–Fe–FeNi 3 @AC (4.54 mF cm −2 ), demonstrating an enhanced ECSA with more active sites, which may benefit from the hierarchical porous architecture caused by NaHCO 3 . Impressively, the OER catalytic activity of Ni 5 P 4 /Ni 2 P–FeNi@C in this work is comparable to and may even outperform recently reported alloy- and phosphide-composited catalysts ( Figure 6 f and Table 1 ) [ 14 , 19 , 22 , 29 , 30 , 32 , 33 , 34 , 35 ].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…As shown in Figure 6 e, Ni 5 P 4 /Ni 2 P–FeNi@C presents a larger C dl value (8.01 mF cm −2 ) than Ni 5 P 4 /Ni 2 P–Fe–FeNi 3 @AC (4.54 mF cm −2 ), demonstrating an enhanced ECSA with more active sites, which may benefit from the hierarchical porous architecture caused by NaHCO 3 . Impressively, the OER catalytic activity of Ni 5 P 4 /Ni 2 P–FeNi@C in this work is comparable to and may even outperform recently reported alloy- and phosphide-composited catalysts ( Figure 6 f and Table 1 ) [ 14 , 19 , 22 , 29 , 30 , 32 , 33 , 34 , 35 ].…”
Section: Resultssupporting
confidence: 84%
“…To further evaluate the catalytic properties, the OER dynamics were evaluated by Tafel slope. Ni 5 P 4 /Ni 2 P–FeNi@C exhibited the lowest Tafel slope of 46 mV dec −1 , as shown in Figure 6 c, indicating that Ni 5 P 4 /Ni 2 P–FeNi@C has the most rapid kinetics for the OER process [ 30 ]. These results may be caused by the in situ formation of NaCl and NaHCO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…4) Less mass transport between the alloy and the electrode. [144][145][146][147] Therefore, efficient approaches need to be developed to optimize the OER activities of NiFe alloys. Wang and co-workers found that hcpphase NiFe NPs encapsulated in N-doped carbon (NC) exhibited an unexpectedly low overpotential of 226 mV at 10 mA cm −2 in 1.0 m KOH as the electrolyte, in addition to an excellent stability during 35 h of continuous operation at a current density of 20 mA cm −2 .…”
Section: The Nife Alloys and The Nife-based Nonoxide Familymentioning
confidence: 99%
“…8,19−24 In light of adverse Fenton reaction from Fe ions, 25 poisoning effect from leached Cu ions, 26 and inherent disordered structure of PtNi 3 , 27 PtCo 3 NP emerges as a promising cathode for fuel cells because of the low cost and mildness of Co 2+ to the proton-exchange membrane. Very little effort has been devoted to PtCo 3 , and previously reported dealloyed PtCo 3 NPs are in disordered face-centered cubic (fcc) structure; 28,29 traditional synthetic strategies, for example, impregnation method, 10,19 KCl matrices, 30 oxide coating, 31 freeze-drying− annealing, 28 and self-assembly, 32,33 show practicability for nanocatalyst preparation, meanwhile they suffer from complexity, time-consuming process, large particle sizes, or incomplete removal of oxide and Cl − . Hence, new strategies should be exploited to synthesize small-sized well-dispersed ordered Ptbased NPs in a practical and easily operated way.…”
Section: Introductionmentioning
confidence: 99%
“…Very little effort has been devoted to PtCo 3 , and previously reported dealloyed PtCo 3 NPs are in disordered face-centered cubic (fcc) structure; , thus, it remains essential to construct ordered intermetallic PtCo 3 NPs. Furthermore, although traditional synthetic strategies, for example, impregnation method, , KCl matrices, oxide coating, freeze-drying–annealing, and self-assembly, , show practicability for nanocatalyst preparation, meanwhile they suffer from complexity, time-consuming process, large particle sizes, or incomplete removal of oxide and Cl – . Hence, new strategies should be exploited to synthesize small-sized well-dispersed ordered Pt-based NPs in a practical and easily operated way.…”
Section: Introductionmentioning
confidence: 99%